A review on experimental surgical models and anesthetic protocols of heart failure in rats - Farag, Ahmed; Mandour, Ahmed S.; Hendawy, Hanan; Elhaieg, Asmaa; Elfadadny, Ahmed; Tanaka, Ryou (Frontiers in Veterinary Science, 2023)
Abstract Heart failure (HF) is a serious health and economic burden worldwide, and its prevalence is continuously increasing. Current medications effectively moderate the progression of symptoms, and there is a need for novel preventative and reparative treatments. The development of novel HF treatments requires the testing of potential therapeutic procedures in appropriate animal models of HF. During the past decades, murine models have been extensively used in fundamental and translational research studies to better understand the pathophysiological mechanisms of HF and develop more effective methods to prevent and control congestive HF. Proper surgical approaches and anesthetic protocols are the first steps in creating these models, and each successful approach requires a proper anesthetic protocol that maintains good recovery and high survival rates after surgery. However, each protocol may have shortcomings that limit the study’s outcomes. In addition, the ethical regulations of animal welfare in certain countries prohibit the use of specific anesthetic agents, which are widely used to establish animal models. This review summarizes the most common and recent surgical models of HF and the anesthetic protocols used in rat models. We will highlight the surgical approach of each model, the use of anesthesia, and the limitations of the model in the study of the pathophysiology and therapeutic basis of common cardiovascular diseases.